Dinasti Politik dalam Kepemimpinan Lokal: Studi Persepsi Masyarakat Sukoharjo terhadap Etik Suryani sebagai Bupati - Atsmar Hidayati Utomo; Rina Martini (Journal of Politic and Government Studies, 2026)
Political dynasties remain a significant phenomenon in Indonesia’s local democratic practices. Sukoharjo Regency represents one of the regions experiencing the continuity of kinship-based power through the election of Etik Suryani as Regent, who has a familial relationship with the previous regional leader. This study aims to analyze public perceptions of political dynasties and Etik Suryani’s leadership within the context of local politics. This research employs a descriptive quantitative approach using a Liker-scale questionnaire distributed to 100 respondents selected through convenience sampling. Data were analyzed using descriptive statistical methods. The findings sampling indicate that the public demonstrates a relatively high level of cognitive awareness regarding the existence of political dynasties. At the affective level, the community tends to feel uncomfortable, with kinship-based politics. Public Political support for Etik Suryani largely pragmatic, primarily based on performance evaluation and program continuity rather than emotional loyalty to a political family. Her leadership is perceived as moderately positive, although respondents also recognize indications of elite capture, particularly in the form of family network dominance and limited opportunities for new political actors. T study concludes that Sukoharjo society is critical yet pragmatic toward political dynasties, accepting their presence as long as governmental performance is considered adequate. These findings suggest that political legitimacy at the local level is increasingly shaped by performance-based evaluation rather than solely by kinship ties, although the risk of power concentration within elite family circles remains.